The Companion to Language Assessment 2013
DOI: 10.1002/9781118411360.wbcla035
|View full text |Cite
|
Sign up to set email alerts
|

Administration, Scoring, and Reporting Scores

Abstract: This chapter covers administration, scoring, and reporting scores from language tests and examinations. Procedures typically used in major language examinations and small‐scale classroom testing and assessment are both covered. It is argued that the administration, scoring, and reporting procedures are highly dependent on the purpose and stakes of the assessment. Selected national and international guidelines of good practice are reviewed to see what they have to say about these phases of the assessment proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In traditional penand-pencil testing, score reports present students' performance summary as scores or grades sometimes accompanied by a cursory description of the test and of the meaning of the grades. However, score reports can be delivered in an electronic (i.e., digital) format, especially if they originate from CBT (Huhta, 2013). Such reports can include interactive elements (e.g., visualizations and tables) that could engage students in interpreting and understanding their feedback.…”
Section: Computer-based Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…In traditional penand-pencil testing, score reports present students' performance summary as scores or grades sometimes accompanied by a cursory description of the test and of the meaning of the grades. However, score reports can be delivered in an electronic (i.e., digital) format, especially if they originate from CBT (Huhta, 2013). Such reports can include interactive elements (e.g., visualizations and tables) that could engage students in interpreting and understanding their feedback.…”
Section: Computer-based Testingmentioning
confidence: 99%
“…Moreover, there is a lack of empirical studies that address this gap adequately in the literature. Another important challenge in CBT-based score reporting is the communication of assessment results that facilitates meaningful interpretation with the aim to improve the validity of assessments (Cohen and Wollack, 2006, p. 380;Ryan, 2006;Huhta, 2013;AERA, 2014). Previous research has already shown that there is large variability in the delivery and communication of assessment results to students (Knupp and Ainsley, 2008;Zenisky and Hambleton, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Another example of incorporating indigenous assessment criteria into language testing is the research done by Pill (2016 Messick Kane (1992Kane ( , 2004) (argument-based approach) Kane,1992 ( interpretive argument (1) ) (Huhta, 2014). Test feedback is a crucial stage in diagnostic language assessment, which consists of three phases of diagnosis, feedback, and remedial learning (Lee, 2015).…”
Section: Development Of Rating Scalesmentioning
confidence: 99%
“…test results or providing feedback on test results (i.e., test feedback) is essential to test use in both classroom and standardized testing(Huhta, 2014). Effective test feedback assists stakeholders (i.e., test takers, parents, teachers, administrators, policy makers, and other test users) in using test scores appropriately.…”
mentioning
confidence: 99%
See 1 more Smart Citation